王朔现象与中国当代大众文化 （1984-2000）= Rethinking Wang Shuo : popular culture in contemporary China (1984-2000) - 王一敏 Wang, Yimin (2008)
Contextualize Wang Shuo's works as a cultural product in contemporary China through interdisciplinary perspectives with focus on his negotiation of identity. Examination of popular culture in mainland China and identify characteristics of ideological and cultural changes.